Role of Tocilizumab in Down Regulating sCD163 Plasmatic Levels in a Cohort of COVID-19 Patients - Marocco, Raffaella; Carraro, Anna; Zingaropoli, Maria Antonella; Nijhawan, Parni; Tortellini, Eeva; Guardiani, Mariasilvia; Mengoni, Fabio; Zuccalà, Paola; Belvisi, Valeria; Kertusha, Blerta; Parente, Alberico; Del Borgo, Cosmo; et al. (Frontiers in Immunology, 2022)
Background CD163, a haptoglobin-hemoglobin scavenger receptor mostly expressed by monocytes and macrophages, is involved in the regulation of inflammatory processes. Following proteolytic cleavage after pro-inflammatory stimulation, CD163 is shed from the cell surface and its soluble form in plasma, sCD163, is a biomarker of monocyte/macrophage lineage activation. The assessment of sCD163 plasmatic levels in an early stage of the disease could have clinical utility in predicting the severity of COVID-19 pneumonia. The use of tocilizumab (monoclonal antibody anti-IL-6 receptor) in COVID-19 patients reduces lethality rate at 30 days. The aim of the study was to investigate the effect of tocilizumab on sCD163 plasmatic levels in a cohort of COVID-19 patients. Methods In COVID-19 patients, on hospital admission (T0), after 7 days from hospitalization (T7) and after 45 days from discharge (T45) sCD163 plasmatic levels were evaluated, along with other laboratory parameters. COVID-19 patients were stratified into tocilizumab (TCZ) and non-tocilizumab (non-TCZ) groups. TCZ group was further divided into responder (R) and non-responder (NR) groups. Patients who died or required mechanical ventilation were defined as NR. As control group, healthy donors (HD) were enrolled. Results Seventy COVID-19 patients and 47 HD were enrolled. At T0, sCD163 plasmatic levels were higher in COVID-19 patients compared to HD (p<0.0001) and the longitudinal evaluation showed a reduction in sCD163 plasmatic levels at T7 compared to T0 (p=0.0211). At T0, both TCZ and non-TCZ groups showed higher sCD163 plasmatic levels compared to HD (p<0.0001 and p=0.0147, respectively). At T7, the longitudinal evaluation showed a significant reduction in sCD163 plasmatic levels (p=0.0030) only in the TCZ group, reaching levels comparable to those of HD. Conversely, not statistically significance in non-TCZ group was observed and, at T7, a statistically significance was found comparing non-TCZ group to HD (p=0.0019). At T0, R and NR groups showed not statistically significance in sCD163 plasmatic levels and both groups showed higher levels compared to HD (p=0.0001 and p=0.0340, respectively). The longitudinal evaluation showed significant reductions in both groups (R: p=0.0356; NR: p=0.0273) independently of the outcome. After 45 days of follow-up sCD163 plasmatic levels remain stable. Conclusion sCD163 plasmatic levels are increased in COVID-19 pneumonia and is efficiently down-regulated by tocilizumab treatment regardless of the clinical outcome.